Narrative Structure of Babad Cirebon: Vladimir Propp Analysis - Widianti, Nurhannah; Indiatmoko, Bambang (Pascasarjana Universitas Negeri Semarang, 2018)
The purpose of this research is to analyze babad story of Cirebon based on Propp theory’s in order determine the function of the perpetrator, to formulate the story frame, to distribute the function among actors, and to determine the scheme of story movement. The results showed that the story contained 17 functions of the actors in the form of the absence prohibition, violation, deficiency, intermediary event of contact, the beginning of reply, departure, first donor, reaction of the hero, acceptance of magic tools, unrecognized returns, the heroes were given a difficult task, tasks completed, completion, incarnation, and married heroes. The frame of the babad story of Cirebon begined with the description of the King Prabu Siliwangi's son who still live in the palace and the meeting situation, followed by a series of abuser functions contained in the babad story of Cirebon. Furthermore, the story is closed by the information that would be the leader of Cirebon named Syarif Hidayatullah. The babad story of Cirebon there contained the environment of donor actions, environmental auxiliary measures, the environment of the acts of daughters and their fathers, the environment of intermediary acts, and the environment of the hero's actions. Meanwhile, the babad story of Cirebon consisted of a storyline with four interrelated movements. From those scheme, the essense of the babad story of Cirebon could be known.